P303 Ultrasound is effective to identify mucosal healing in Crohn's disease patients : results of a cross-sectional study. (30th January 2023) - Yzet, C; Brazier, F; Hautefeuille, V; Decrombecque, C; Sarba, R; aygalenq, P; Venezia, F; Buisson, A; Pichois, R; Michaud, A; Fumery, M
Abstract: Background: Endoscopy is still the gold-standard to assess disease activity in Crohn's disease (CD). Its invasiveness, acceptability and cost limit its use in the era of tight control and treat-to-target. Fecal calprotectin and intestinal ultrasound (IUS) are non-invasive alternatives to colonoscopy to assess disease activity. The objective of this study was to evaluate the performance of IUS and fecal calprotectin to assess mucosal healing in CD. Methods: All consecutive CD patients who underwent colonoscopy for mucosal healing assessment and IUS and/or calprotectin within 4 weeks between September 2019 and April 2022 were included in a prospective cohort. Bowel wall thickness (BWT) and color doppler signal (CDS) were assessed on each segment. Endoscopic mucosal healing was defined by a CDEIS score < 3. Results: A total of 153 patients were included, of whom 122 had endoscopic mucosal healing. Eighty-two (53.6%) were female, the median age and disease duration were respectively 36 years (IQR, 28-46) and 10 years (IQR, 4-19). Respectively 56 (56/120, 46.7%) and 93 (93/120, 77.5%) patients presented a BWT < 3 mm and an absence of CDS. The sensitivity (Se), specificity (Sp), positive predictive value (PPV) and negative predictive value (NPV) of BWT < 3 mm to predict endoscopic mucosal healing were 56%, 88%, 95% and 36% (patients misclassified as endoscopic mucosal healing 2.5%). The association of an absent of CDS with a normal BWT did not modify the performances. For a calprotectin < 250 µg/g, The Se, Sp, PPV and NPV were respectively 91%, 63%, 90% and 67% for (patients misclassified 8%). The association of a calprotectin < 250 µg/g, with a BWT < 3 mm and the absence of CDS increased the specificity and the PPV (Se 58%, Sp 95%, PPV 97%, VPN 43%, patients misclassified 1%). Conclusion: Ultrasound is an efficient non-invasive tool to identify patients with Crohn's disease who have achieved endoscopic mucosal healing.